Protease-Activated Receptor-1 Antagonist Protects Against Lung Ischemia/Reperfusion Injury - Chu, Shi-Jye; Tang, Shih-En; Pao, Hsin-Ping; Wu, Shu-Yu; Liao, Wen-I (Frontiers in Pharmacology, 2021)
Protease-activated receptor (PAR)-1 is a thrombin-activated receptor contributing to an essential role in ischemia/reperfusion (IR)-induced acute inflammation. PAR-1 antagonist has been shown to alleviate injuries in various IR models. However, the effect of PAR-1 antagonist on IR-induced acute lung injury (ALI) has not yet been elucidated. This study aimed to investigate whether PAR-1 inhibition could attenuate lung IR injury. Lung IR was induced in an isolated perfused rat lung model. Male rats were treated with the specific PAR-1 antagonist SCH530348 (vorapaxar) or vehicle, followed by ischemia for 40 min and reperfusion for 60 min. To examine the role of PAR-1 and the mechanism of SCH530348 on lung IR injury, Western blotting and immunohistochemical analysis of lung tissue were performed. In vitro, mouse lung epithelial cells (MLE-12) were treated with SCH530348 or vehicle and subjected to hypoxia-reoxygenation (HR). We found that SCH530348 decreased lung edema and neutrophil infiltration, attenuated thrombin production, reduced inflammatory factors, including cytokine-induced neutrophil chemoattractant-1, interleukin-6 and tumor necrosis factor-α, mitigated lung cell apoptosis, and downregulated the phosphoinositide 3-kinase (PI3K), nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) pathways in IR-injured lungs. In addition, the SCH530348 prevented HR-induced NF-κB activation and inflammatory chemokine production in MLE12 cells. Our results demonstrate that SCH530348 exerts protective effects by blocking PAR-1 expression and modulating the downstream PI3K, NF-κB and MAPK pathways. These findings indicate that the PAR-1 antagonist protects against IR-induced ALI and is a potential therapeutic candidate for lung protection following IR injury.